Hjemme igjen - Sandvik, Birte (Tidsskrift for kulturforskning, 2009)
The article discusses the methods used to furnish the apartments in the city residential building Wessels gate 15 that was moved from down town Oslo to Norsk Folkemuseum [Norwegian Museum of Cultural History] in 1998. The museum's collecting strategies and the museum's contact and relationship with the various donors to create credible exhibitions are presented. The various strategies employed to find sources for the creation of these "homes" and the challenges the museum was presented with in the creation of credible presentations of Norwegian residential history, are outlined.